CASH FLOW, GROWTH OPPORTUNITY, GOVERNMENT BANK RELATIONSHIP, AND INVESTMENT - Setiawan, Rahmat; Ratri, Indira Nuansa (Economic Faculty, Attahiriyah Islamic University, 2020)
This study aims to examined the effect of cash flow and growth opportunity to the investment, and whether the exclusive relationship owned by the company with a government owned bank relationship moderates the effect of cash flow and growth opportunity on investment. This study used a sample of data from 101 manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2017. The multiple linear regression results show that cash flow and growth opportunity have a significant positive effect on investment, the government owned bank relationship weakens the effect of cash flow on investment but strengthens growth opportunity's influence on investment. This means that if the company has an exclusive relationship with a state-owned bank, it will reduce the dependence of cash flow to invest and increase investment opportunities.